An ethnographic exploration of the Yoruba social construction of names. Issue 1 (2nd January 2023) - Oluyemi, Joseph A.
ABSTRACT: This study explored the traditional Yoruba social construction of names, the evolving contemporary Yoruba religious names and its implications on the Yoruba traditional culture. Published articles on Yoruba traditional names and contemporary Yoruba religious names were reviewed. Articles were sourced from online journals and textbooks from which data useful to the topic were retrieved. Publication by relevant bodies on Yoruba names were equally reviewed and relevant information retrieved from them while the study employed the social construction theory. The study revealed that socially constructed traditional Yoruba names such as orukọ àmútòrunwá (pre-ordained names), orúkọ àbísọ (ascribed or acquired names), orúkọ oríkì (praise names) and orúkọ àbíkú (names given to children who die repeatedly before puberty) are fast fading away and are being replaced with Olú, Olúwa, Olórun, to reflect the contemporary beliefs. The study concludes that with the advent of modernity, Yoruba traditional social construction of names is fast losing its place to Yoruba religious names. It is recommended that this be addressed in order to forestall extinction of traditional Yoruba names and loss of cultural identity that may arise.